Computer aided tool support (CATS) for information strategy planning (ISP): Generating application portfolio for business area analysis - Wahid, Juliana; Md Dahalin, Zulkhairi; Idrus, Mohd Rushdi; Omar, Mohd Adan (Faculty of Information Technology Universiti Utara Malaysia, 2008)

(untitled)
Information Strategy Planning (ISP) is concerned with an organization's plan to acquire appropriate "IT blueprint" encompassing suitable hardware,software and telecommunication facilities for the utilization of applications required by the business with adequate support structure. The purpose is to determine the enterprise's business goals and a high-level overview of the enterprise, its funtions,data and information needs. This research builds an ISP engine, i.e. the Computer Aided Tool Support (CATS) that has the capability to generate application portfolios that can support the business strategy of the enterprise. Application portfolio is a major part of the ISP deliverables which can significantly aid in formulating suitable strategies for IT supply and IT support structure. CATS will help to facilitate End-User Computing as a tool not only to ease end-users in planning for their IT adoption, but also to ensure that their IT investment is aligned to business goals and strategies. CATS will be able to help the Small Medium Enterprise (SME) companies and other organizations in their information systems planning so that they can achieve their missions and objectives in more efficient way.